Long-term safety and tolerability of apremilast in patients with psoriasis: Pooled safety analysis for ≥156 weeks from 2 phase 3, randomized, controlled trials (ESTEEM 1 and 2) - Crowley, Jeffrey; Thaçi, Diamant; Joly, Pascal; Peris, Ketty; Papp, Kim A.; Goncalves, Joana; Day, Robert M.; Chen, Rongdean; Shah, Kamal; Ferrándiz, Carlos; Cather, Jennifer C. (Journal of the American Academy of Dermatology, 2017)
Randomized, controlled trials demonstrated efficacy and safety of apremilast for moderate-to-severe plaque psoriasis and psoriatic arthritis. Assess long-term safety of oral apremilast in psoriasis patients. Safety findings are reported for 0 to ≥156 weeks from the Efficacy and Safety Trial Evaluating the Effects of Apremilast in Psoriasis (ESTEEM) 1 and 2. The 0 to ≥156–week apremilast-exposure period included 1184 patients treated twice daily with apremilast 30 mg (1902.2 patient-years). During 0 to ≤52 weeks, the adverse events (AEs) that occurred in ≥5% of patients included diarrhea, nausea, upper respiratory tract infection, nasopharyngitis, tension headache, and headache. From 0 to ≥156 weeks, no new AEs (affecting ≥5% of the population) were reported. AEs, serious AEs, and study drug discontinuations caused by AEs did not increase with long-term exposure. During the 0 to ≥156–week period, the rates of major cardiac events (exposure-adjusted incidence rate [EAIR] 0.5/100 patient-years), malignancies (EAIR 1.2/100 patient-years), depression (EAIR 1.8/100 patient-years), or suicide attempts (EAIR 0.1/100 patient-years) did not increase in comparison with the rates found during the 0 to ≤52–week period. No serious opportunistic infections, reactivation of tuberculosis, or clinically meaningful effects on laboratory measurements were reported. This study had a high dropout rate (21% of patients ongoing >156 weeks); most were unrelated to safety concerns. Apremilast demonstrated an acceptable safety profile and was generally well tolerated for ≥156 weeks.